2020
DOI: 10.1155/2020/1243953
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Saliva and Cariogenic Microbiota on the Chemotherapy-Induced Oral Mucositis in Oncopediatric Patients: A Preliminary Longitudinal Study

Abstract: The aim of this study is to evaluate salivary and microbiological parameters of pediatric oncological patients and their correlation with severe oral mucositis (SOM).This study aims to evaluate the salivary parameters and cariogenic microbiota of pediatric oncological patients and their correlation with severe oral mucositis (SOM). A preliminary longitudinal study The prospective study included patients in the age range from 4 to 18 years (n = 26), with diagnosis of primary cancer, who were followed up before … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 36 publications
0
12
0
1
Order By: Relevance
“…This induction phase is known to be characterized by intense medication protocols with high doses of cytotoxic chemotherapy agents, attempting to achieve complete remission and restore normal hematopoiesis of these patients. 35 Indeed, our preliminary study 14 and others 12,36 have shown that the induction phase is a critical time for hematological cancer treatment with more impact on oral physiological parameters such as saliva, oral microbiota, and host cell interactions. Although some previous studies have also evaluated these response variables (USF and oral streptococci load), the results are crosssectional 11,13,18 or longitudinal of short-term periods (50 days for the endpoint), 9,22,37,38 which are not able to completely evaluate the impact of cancer therapy on different follow-up time-points.…”
Section: Discussionmentioning
confidence: 83%
See 4 more Smart Citations
“…This induction phase is known to be characterized by intense medication protocols with high doses of cytotoxic chemotherapy agents, attempting to achieve complete remission and restore normal hematopoiesis of these patients. 35 Indeed, our preliminary study 14 and others 12,36 have shown that the induction phase is a critical time for hematological cancer treatment with more impact on oral physiological parameters such as saliva, oral microbiota, and host cell interactions. Although some previous studies have also evaluated these response variables (USF and oral streptococci load), the results are crosssectional 11,13,18 or longitudinal of short-term periods (50 days for the endpoint), 9,22,37,38 which are not able to completely evaluate the impact of cancer therapy on different follow-up time-points.…”
Section: Discussionmentioning
confidence: 83%
“…21,22 Furthermore, cariogenic-associated microbiota may also induce harmful effects in the severity of chemotherapyrelated oral diseases. 18 In fact, our preliminary study 14 showed a trend towards a progressive total load of salivary Streptococcus spp. (TS) in childhood cancer, and this finding needed to be more investigated in hematological pediatric patients.…”
Section: Introductionmentioning
confidence: 92%
See 3 more Smart Citations